Studien zum Gottesbild im Johannesevangelium - Burz-Tropper, Veronika (Mohr Siebeck, 2020)
The whole of the New Testament is occupied with God and the discussion of him. New Testament scholarship, however, barely treats God the Father as a separate subject. Because His significance is not to be neglected, the contributors to this volume turn their attention to illuminating God the Father from various angles.
Description based on print version record.
KU Open Services
Keywords: Religion / Theology; Religion; Electronic books